Kontribusi Terapi Kelompok Role Play terhadap Skill Interaksi Sosial Pasien Skizofrenia - Dewi Puspita Wardani; Rita Untari (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Schizophrenia is a psychotic disorder characterized by major disturbances in thought, emotion, and behavior. In severe cases, patients lose touch with reality, resulting in abnormal thinking and behavior. Common problems in schizophrenia include neglect of appearance, social withdrawal, incoherence, catatonia, anxiety, and hallucinations. Group role-playing therapy is conducted in a group with several members who dramatize a scenario or role that has a purpose and rules, and involves elements of enjoyment. Objectives: This study aims to determine the effect of group role-playing therapy on social interaction skills in schizophrenia patients at Dr. Radjiman Wediodiningrat Mental Hospital, Lawang. The role-playing interventions included portraying folklore characters, acting out scenarios, and composing and reciting poetry. A purposive sampling technique was used to select 25 patients with schizophrenia. The instrument used was the SIAS (Social Interaction Anxiety Scale), administered before and after the intervention. Methods: This study was a pre-experimental study using a one-group pre- and post-test design. The results of the normality test showed that the data were not normally distributed, so the nonparametric Wilcoxon test was used. Results: The Wilcoxon test showed a p-value of 0.001 (p<0.05), indicating a significant difference in social interaction skills before and after role-playing group therapy at Dr. Radjiman Wediodiningrat Mental Hospital, Lawang. Conclusion: This study demonstrates the effect of role-playing group therapy on social interaction skills in schizophrenia patients. Keywords: Group Role-Playing Therapy, Social Interaction, Schizophrenia.